The effect of age and technological change on motor vehicle emissions - Zachariadis, Theodoros; Ntziachristos, T.; Samaras, Zissis (My University, 2001)
The paper outlines the basic effects of aging and technological substitution of motor vehicles on their air emissions. The analysis is facilitated with the aid of an existing model that simulates the internal dynamics of vehicle populations and performs emission calculations. The renewal rate of vehicles is modeled and associated uncertainties are demonstrated. The sensitivity of the system to specific age and technological parameters is examined. The impacts of emissions deterioration, implementation of inspection and maintenance programs and introduction of cleaner fuels are studied.
Keywords: Deterioration; Lifetime; Mobile sources; Scrappage; Vehicle emissions